Chomsky's politics - Rai, Milan (London : Verso, 2000)
A survey of Noam Chomsky's political writing. This book is an introduction to the basic ideas underlying this intellectual's critiques of the mass media and the new world order. It includes a summary of his visions of the future and his own brand of libertarian socialism
Keywords: Chomsky, Noam, -- 1928-.